A Lifetime Devoted to Folklore: Kemal Akca and His Works - Harmanci, Meric; Arican, Sumeyya (Rector CIU Cyprus Int Univ, 2025)
During and after the establishment of the Republic of Turkiye, the starting point of the country's intellectuals and the consciousness they wanted to implant in the people were national values, the Turkish language, and culture. The first steps to give national identity and consciousness were mainly carried out through language, literature, history, and folklore; in this direction, collective memory and cultural treasures were consulted. We conducted this study on the life and works of Ali Kemal Akga, who has carried out essential studies by acting with the awareness that folklore is an important source in revealing the collective memory. Akga, one of the most critical folklore researchers and writers of the 1940s, was the owner and editor-in-chief of Folklor Postas & imath;, the second regularly published folklore magazine in Turkiye. Although he published a folklore magazine in the years when Turkish folklore studies gained momentum, prepared books on folklore, and wrote articles in newspapers and magazines, there is no detailed and collective examination of his work. In this study, we aimed to increase the visibility of a lifetime dedicated to folklore and his works by examining Akga's articles written in magazines and newspapers and his books. We also analyzed the content of the articles and classified them under seven headings. This classification is also remarkable as an example of how the founding intellectuals of the Republic paid attention to folklore and how they benefited from the cadres of folklore to create a national spirit.
Keywords: KemalAk & ccedil; a; folklore; national consciousness; Folklor Postas & imath; Konya; Arts & Humanities - Other Topics; Literature